Phf8 loss confers resistance to depression-like and anxiety-like behaviors in mice - Ryan M. Walsh (Nature Portfolio, 2017)
Mutation of the human genePHF8, encoding a histone demethylase, is linked to cognitive defects but its role in development is unclear. Here, the authors show that Phf8deletion in mice causes no overt developmental defects but confers resilience to depression, likely through increased serotonin signalling.